Biotechnology for the Environment - Nikodinovic-Runic, Jasmina; Topakas, Evangelos; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Biotechnology for the Environment is an open access, peer-reviewed journal featuring studies that explore the advancements and applications of biotechnology for environmental management, protection, and sustainability, including agriculture and forestry. The journal also aims to advance the discussion around the complex interplay between environmental issues and bioproduction through insightful and diverse research. The main areas in scope are, but not only limited to: Environmental clean-up, decontamination and improvement of water and wastewater, air, and soil, including pollution prevention and treatment, bioremediation, and biodegradation of pollutants and emerging contaminants Biotechnology for sustainable water and land management Biotechnology for agriculture and forestry, including genetic modification Resources and waste, hazardous waste management, and landfill management Environmental biotechnology for metagenome, ecogenomics, and epigenetics Sustainable catchments and renewable energy (such as biotreatment in water harvesting, wetland systems management, conversion of gaseous pollutants to biofuels and bioenergy, etc.) Industrial biotechnology and bioproduction supporting sustainability and responsible environmental management Biotechnology for production of biodetergents, biopesticides and biofertilizers Life cycle assessment and environmental impact analysis Policy issues and debates A key aim of Biotechnology for the Environment is to promote the visibility and reach of valid, diverse, and innovative research. While the main focus remains on research and reviews of wide applicability and relevance, the journal is also open to consider confirmatory research, short communications, data analyses and discussions, local studies of interest for specific regions, and case studies where the authors are able to show meaningful relevance to the broader discussion around key topics in environmental biotechnology. Biotechnology for the Environment aims to highlight innovations that promote clean water and sanitation, sustainable cities and communities, life below water and life on land, according to the Sustainable Development Goals framework. Furthermore, the scope and the research published in Biotechnology for the Environment aims to resonate with the principles of Green Chemistry, particularly with the focus on safer solvents and reactions, energy efficiency, renewable feedstock, degradation after use, and avoidance of chemical derivatives.
Keywords: Biotechnology; Environmental engineering; Biotechnology; Bioremediation; Renewable energy sources; Microbiology; Plant biotechnology; Biotechnology; Environmental Engineering/Biotechnology.; Renewable Energy; Microbiology; Plant Biotechnology